Digitalisasi Transportasi UM Berbasis IoT untuk Mendukung Pengembangan Smart Campus yang Secara Lebih Berkelanjutan - Lianna Zahrotun Nizar; Mayyasa Andira Fatiha; Dani Irawan (PT. Alahyan Publisher, 2026)
The increasing use of private motor vehicles within Universitas Negeri Malang has led to traffic congestion, air pollution, and a decline in the quality of public spaces. This situation highlights the need to transform the campus mobility system into a transportation model that is more efficient, safe, and sustainable. This proposal introduces the Smart Mobility UM innovation based on integrated Internet of Things (IoT) technology, which includes the provision of campus bicycles equipped with QR Codes and GPS, the operation of electric shuttles, the improvement of pedestrian pathways, and the gradual implementation of motor-vehicle-free zones. All services will be connected through the Go Green UM application, functioning as a center for rentals, tracking, and the management of green transportation. The program also involves training for the academic community, collaboration with technology partners, and continuous evaluation to maintain the effectiveness of the system. The implementation of this smart transportation system is expected to reduce emissions, enhance mobility comfort, and support the achievement of SDG 11 as well as the development of a Smart & Green Campus at Universitas Negeri Malang.